The language of pop culture / edited by Valentin Werner - Werner, Valentin (New York, NY ; Milton Park, Abingdon, Oxon : Routledge, Taylor & Francis Group, 2018)
This collection brings together contributions from both leading and emerging scholars in one comprehensive volume to showcase the richness of linguistic approaches to the study of pop culture and their potential to inform linguistic theory building and analytical frameworks. The book features examples from a dynamic range of pop culture registers, including lyrics, the language of fictional TV series, comics, and musical subcultures, as a means of both providing a rigorous and robust description of these forms through the lens of linguistic study but also in outlining methodological issues involved in applying linguistic approaches. The volume also explores the didactic potential of pop culture, looking at the implementation of pop culture traditions in language learning settings. This collection offers unique insights into the interface of linguistic study and the broader paradigm of pop culture scholarship, making this an ideal resource for graduate students and researchers in applied linguistics, English language, media studies, cultural studies, and discourse analysis.
Part I: Context1. Linguistics and pop culture: Setting the scene(s) Valentin Werner2. Pop culture and linguistics - is that, like, a thing now? Joe TrottaPart II: Comics3. Pardon my French... and German... and Spanish...: (Mis)speaking in tongues in Marvel comics Shane Walshe4. Linguistic discourse in web comics: Extending conversation and narrative into alt-text and hidden comics Frank BramlettPart III: Music and Lyrics5. Pop culture and the globalization of non-standard varieties of English: Jamaican Creole in German reggae subculture Michael Westphal6. "Britpop is a thing, damn it": On British attitudes toward American English and an Americanized singing style Lisa JansenPart IV: TV and Movies7. Variation in movies and television programs: The impact of corpus sampling Marcia Veirano Pinto8. Verbal humor in crime drama television: A cognitive-linguistic approach to popular TV series Christoph SchubertPart V: Pop meets EFL9. An analysis of pop songs for teaching English as a foreign language: Bridging the gap between corpus analysis and teaching practice Theresa Summer10. Song lyrics: From Multi-Dimensional Analysis to the foreign language classroom Patricia Bertoli11. (Im)politeness rituals in The Young Pope and teaching pragmatics Silvia BrutiEpilogue12. Analyzing pop culture Monika Bednarek
Includes bibliographical references and index.
ENH
Keywords: English language -- Social aspects; English language -- Variation; Language and languages in popular culture